Multilayer electronic component
By using glass containing Ba, Zn and Si in the contact layer and base electrode layer of the multi-layer ceramic capacitor, and adjusting the molar ratio of Ba to Si, the problem of softening and wettability of the external electrodes in the prior art is solved, and better sealing and corrosion resistance are achieved.
Patent Information
- Application Number
- JP2024122629
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-26
- Filing Date
- 2024-07-29
- Publication Date
- 2025-04-08
AI Technical Summary
The external electrodes of the existing multi-layer ceramic capacitors soften at high temperatures and reduce wettability to copper, resulting in the inability to sufficiently fill the gaps in the thermal power electrodes and the sealing properties cannot be guaranteed.
The first glass containing Ba, Zn and Si is used as the contact layer, and the second glass containing Ba and Si is used in the base electrode layer. By adjusting the molar ratio of Ba to Si in both, the average ratio M1/M2≧1.5 is improved to improve sealing and corrosion resistance.
It effectively prevents the penetration of external moisture and plating solutions, and improves the reliability and sealing of multi-layer ceramic capacitors.
Smart Images

Figure 2025056716000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a multilayer electronic component. [Background technology]
[0002] Multi-layered ceramic capacitors (MLCCs), which are one type of multi-layered electronic component, are chip-type capacitors that are mounted on printed circuit boards of various electronic products, such as imaging devices such as liquid crystal displays (LCDs) and plasma display panels (PDPs), computers, smartphones, and mobile phones, and serve to charge and discharge electricity. Multi-layered ceramic capacitors can be used as components of various electronic devices due to their advantages of being small in size, high capacity, and easy to mount.
[0003] Currently, fired electrodes made of metals such as Cu and glass are mainly used as external electrodes for multilayer ceramic capacitors. The metal components of the fired electrodes provide conductivity to the fired electrodes, while the glass provides adhesion between the fired electrodes and the main body and ensures hermetic sealing by penetrating into the voids within the fired electrodes.
[0004] Generally, silicon oxide, which is a network former, is used as the glass component of the fired electrode. Silicon oxide has strong corrosion resistance, which prevents the glass from being corroded by the plating solution and the resulting penetration of the plating solution.
[0005] However, silicon oxide has a high softening temperature and its wettability to copper (Cu) is reduced, which may cause problems such as not being able to fully fill the voids in the fired electrode and not being able to ensure hermetic sealing of the fired electrode.
[0006] In order to solve these problems, research is being conducted on external electrodes of multilayer ceramic capacitors that can ensure both corrosion resistance and sealing properties by appropriately adding an oxide that functions as a network modifier as a glass component. Summary of the Invention [Problem to be solved by the invention]
[0007] One of the various objects of the present invention is to provide a multilayer electronic component which is excellent in reliability by preventing the penetration of moisture and plating solution from the outside.
[0008] However, the object of the present invention is not limited to the above-mentioned contents, and can be more easily understood in the course of describing specific embodiments of the present invention. [Means for solving the problem]
[0009] One embodiment of the present invention provides a multilayer electronic component comprising: a body including dielectric layers and internal electrodes alternately arranged with the dielectric layers; external electrodes including base electrode layers connected to the internal electrodes; and an interface layer arranged between an end of the dielectric layer and the base electrode layer, the interface layer including a first glass including Ba, Zn, and Si, the base electrode layer including a second glass including Ba and Si, wherein M1 is an average molar ratio (Ba / Si) of Ba to Si contained in the first glass, and M2 is an average molar ratio (Ba / Si) of Ba to Si contained in the second glass, and M1 and M2 satisfy M1 / M2≧1.5. Effect of the Invention
[0010] One of the various effects of the present invention is that it is possible to provide a multilayer electronic component with excellent reliability by preventing the penetration of moisture and plating solution from the outside. [Brief description of the drawings]
[0011] [Figure 1]1 is a perspective view showing a schematic configuration of a multilayer electronic component according to an embodiment of the present invention; [Diagram 2] FIG. 2 is an exploded perspective view showing a schematic view of the main body of FIG. [Diagram 3] 2 is a cross-sectional view that shows a schematic cross section taken along line II' in FIG. 1. [Figure 4] 2 is a cross-sectional view that shows a schematic cross section taken along line II-II' in FIG. 1. [Diagram 5] FIG. 4 is an enlarged view of a K1 region in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the embodiments of the present invention will be described with reference to specific embodiments and the accompanying drawings. However, the embodiments of the present invention can be modified into several other forms, and the scope of the present invention is not limited to the embodiments described below. Furthermore, the embodiments of the present invention are provided to more completely explain the present invention to those skilled in the art. Therefore, the shapes and sizes of elements in the drawings may be enlarged or reduced (or highlighted or simplified) for clearer explanation, and elements indicated by the same reference numerals in the drawings are the same elements.
[0013] In addition, in the drawings, parts that are not relevant to the description are omitted in order to clearly explain the present invention, and the size and thickness of each component shown in the drawings are arbitrarily shown for convenience of explanation, so the present invention is not necessarily limited by the drawings. Furthermore, components having the same function within the same concept may be described using the same reference numerals. Furthermore, throughout the specification, when a part "includes" a certain component, it does not mean that the part excludes other components, but that the part may further include other components, unless otherwise specified to the contrary.
[0014] In the drawings, the first direction can be defined as a thickness T direction, the second direction can be defined as a length L direction, and the third direction can be defined as a width W direction.
[0015] Multilayer Electronic Components FIG. 1 is a perspective view that shows a schematic view of a multilayer electronic component according to one embodiment of the present invention, FIG. 2 is an exploded perspective view that shows a schematic view of the main body of FIG. 1, FIG. 3 is a cross-sectional view that shows a schematic view of a cut section taken along line I-I' in FIG. 1, FIG. 4 is a cross-sectional view that shows a schematic view of a cut section taken along line II-II' in FIG. 1, and FIG. 5 is an enlarged view of area K1 in FIG. 3.
[0016] A multilayer electronic component 100 according to one embodiment of the present invention will be described in detail below with reference to Figures 1 to 5. Also, a multilayer ceramic capacitor will be described as an example of a multilayer electronic component, but the present invention is not limited thereto and can be applied to various multilayer electronic components, such as an inductor, a piezoelectric element, a varistor, or a thermistor.
[0017] A laminated electronic component 100 according to an embodiment of the present invention may include a body 110 including a dielectric layer 111 and internal electrodes 121, 122, external electrodes 131, 132, and interface layers 141, 142.
[0018] Although there is no particular limitation on the specific shape of the body 110, the body 110 may be hexahedral or a similar shape as shown in the figure. Due to shrinkage of the ceramic powder contained in the body 110 during the firing process and grinding of the edges, the body 110 may not be a hexahedral shape with perfectly straight lines, but may be substantially hexahedral.
[0019] The main body 110 may have a first surface 1 and a second surface 2 facing each other in a first direction, a third surface 3 and a fourth surface 4 connected to the first surface 1 and the second surface 1 and 2 and facing each other in a second direction, and a fifth surface 5 and a sixth surface 6 connected to the first surface 1, 2, 3 and 4 and facing each other in the third direction.
[0020] The main body 110 can include a dielectric layer 111 and internal electrodes 121 and 122 that are alternately arranged with the dielectric layer 111. The plurality of dielectric layers 111 forming the main body 110 are in a fired state, and the boundaries between adjacent dielectric layers 111 can be integrated so that they are difficult to confirm without using a scanning electron microscope (SEM).
[0021] The dielectric layer 111 can contain, for example, a perovskite compound represented by ABO3 as a main component. The perovskite compound represented by ABO3 is, for example, BaTiO3, (Ba 1-x Ca x )TiO3 (0 < x < 1) in which Ca (calcium), Zr (zirconium), etc. are partially solid-solved in BaTiO3, Ba(Ti 1-y Ca y )O3 (0 < y < 1), (Ba 1-x Ca x )(Ti 1-y Zr y )O3 (0 < x < 1, 0 < y < 1) or Ba(Ti 1-y Zr y )O3 (0 < y < 1), etc.
[0022] The internal electrodes 121 and 122 can be alternately arranged with the dielectric layer 111 in the first direction, for example. The first internal electrode 121 and the second internal electrode 122, which are a pair of electrodes having different polarities, can be arranged to face each other with the dielectric layer 111 interposed therebetween. The first internal electrode 121 and the second internal electrode 122 can be electrically separated from each other by the dielectric layer 111 disposed therebetween.
[0023] The first internal electrode 121 can be separated from the fourth surface 4 and connected to the first external electrode 131 on the third surface 3 side. The second internal electrode 122 can be separated from the third surface 3 and connected to the second external electrode 132 on the fourth surface 4 side.
[0024] The conductive metal contained in the internal electrodes 121, 122 may be one or more of Ni, Cu, Pd, Ag, Au, Pt, Sn, W, Ti, and alloys thereof, and more preferably contains Ni as a main component, but the present invention is not limited thereto.
[0025] The average thickness td of the dielectric layer 111 does not need to be particularly limited, but can be, for example, 0.1 μm to 10 μm. The average thickness te of the internal electrodes 121 and 122 does not need to be particularly limited, but can be, for example, 0.05 μm to 3.0 μm. The average thickness td of the dielectric layer 111 and the average thickness te of the internal electrodes 121 and 122 can be arbitrarily set according to the desired characteristics and applications. For example, in the case of a high-voltage electric field electronic component to achieve miniaturization and high capacity, the average thickness td of the dielectric layer 111 can be less than 2.8 μm, and the average thickness te of the internal electrodes 121 and 122 can be less than 1 μm. In the case of a small IT electronic component to achieve miniaturization and high capacity, the average thickness td of the dielectric layer 111 can be 0.4 μm or less, and the average thickness te of the internal electrodes 121 and 122 can be 0.4 μm or less.
[0026] The average thickness td of the dielectric layer 111 and the average thickness te of the internal electrodes 121, 122 refer to the size of the dielectric layer 111 and the internal electrodes 121, 122 in the first direction, respectively. The average thickness td of the dielectric layer 111 and the average thickness te of the internal electrodes 121, 122 can be measured by scanning the cross sections of the body 110 in the first direction and the second direction with a scanning electron microscope (SEM) with a magnification of 10,000. More specifically, the average thickness td of the dielectric layer 111 can be measured by measuring the thickness at multiple points of one dielectric layer 111, for example, 30 points equally spaced in the second direction, and then averaging the measured values. Also, the average thickness te of the internal electrodes 121, 122 can be measured by measuring the thickness at multiple points of one internal electrode 121, 122, for example, 30 points equally spaced in the second direction, and then averaging the measured values. The 30 equally spaced points can be designated as a capacitance forming portion Ac. Meanwhile, by performing such average value measurements on 10 dielectric layers 111 and 10 internal electrodes 121, 122, respectively, and then measuring the average values, the average thickness td of the dielectric layers 111 and the average thickness te of the internal electrodes 121, 122 can be further generalized.
[0027] The body 110 may include a capacitance forming part Ac in which a capacitance is formed including first internal electrodes 121 and second internal electrodes 122 arranged alternately with a dielectric layer 111 interposed therebetween, and a first cover part 112 and a second cover part 113 respectively arranged on both sides of the capacitance forming part Ac facing each other in a first direction. The cover parts 112 and 113 may basically serve to prevent damage to the internal electrodes due to physical or chemical stress. The cover parts 112 and 113 may have the same configuration as the dielectric layer 111, except that they do not include internal electrodes.
[0028] The average thickness tc of the cover parts 112, 113 does not need to be particularly limited. That is, the average thickness tc of the cover parts 112, 113 can be set arbitrarily according to the desired characteristics and applications. For example, in order to reduce the size and increase the capacity of the multilayer electronic component, the average thickness tc of the cover parts 112, 113 can be 300 μm or less, 100 μm or less, 30 μm or less, or 20 μm or less, but the present invention is not limited thereto. Here, the average thickness tc of the cover parts 112, 113 means the average thickness of each of the first cover part 112 and the second cover part 113.
[0029] The average thickness tc of the cover parts 112, 113 may mean the average size of the cover parts 112, 113 in the first direction, and may be the average value of the size in the first direction measured at five equally spaced points on the cross-section of the body 110 in the first and second directions.
[0030] The body 110 may include a first margin portion 114 and a second margin portion 115 disposed on both sides of the capacitance forming portion Ac facing each other in the third direction. That is, the margin portions 114 and 115 may refer to regions between both ends of the internal electrodes 121 and 122 and the boundary surface of the body 110 in a cross section obtained by cutting the body 110 in the first and third directions.
[0031] The margin portions 114 and 115 may include the same material as the dielectric layer 111, except that they do not include the internal electrodes 121 and 122. The margin portions 114 and 115 may essentially serve to prevent damage to the internal electrodes 121 and 122 due to physical or chemical stress.
[0032] The margin parts 114 and 115 may be formed by applying a conductive paste for the internal electrodes to the ceramic green sheets and firing them except for the areas where the margin parts are to be formed. Alternatively, in order to suppress steps due to the internal electrodes 121 and 122, the margin parts 114 and 115 may be formed by laminating a single dielectric layer or two or more dielectric layers on both sides of the capacitance forming part Ac facing each other in the third direction, after cutting the laminated internal electrodes 121 and 122 so that they are exposed on the fifth and sixth faces 5 and 6 of the main body.
[0033] The average thickness tm of the margin portions 114, 115 does not need to be particularly limited. That is, the average thickness tm of the margin portions 114, 115 can be set arbitrarily according to the desired characteristics and applications. For example, in order to reduce the size and increase the capacity of the multilayer electronic component, the average thickness tm of the margin portions 114, 115 can be 100 μm or less, 20 μm or less, or 15 μm or less, but the present invention is not limited thereto. Here, the average thickness tm of the margin portions 114, 115 means the average thickness of each of the first margin portion 114 and the second margin portion 115.
[0034] The average thickness tm of the margin portions 114, 115 may mean the average size in the third direction of the margin portions 114, 115, and may be the average value of the size in the third direction measured at five equally spaced points on the cross sections of the body 110 in the first and third directions.
[0035] The external electrodes 131, 132 may be disposed on the third and fourth surfaces 3, 4 of the body 110 and may extend onto portions of the first, second, fifth and sixth surfaces 1, 2, 5, 6. The external electrodes 131, 132 may include a first external electrode 131 disposed on the third surface 3 and a second external electrode 132 disposed on the fourth surface 4.
[0036] The external electrodes 131, 132 may include base electrode layers 131a, 132a connected to the internal electrodes 121, 122 and plating layers 131b, 132b disposed on the base electrode layers 131a, 132a. That is, the first external electrode 131 may include a first base electrode layer 131a connected to the first internal electrode 121 and a first plating layer 131b disposed on the first base electrode layer 131a, and the second external electrode 132 may include a second base electrode layer 132a connected to the second internal electrode 122 and a second plating layer 132b disposed on the second base electrode layer 132a.
[0037] In the drawings, the multilayer electronic component 100 is shown to have a structure having two external electrodes 131, 132, but this is not limited to this, and the number and shape of the external electrodes 131, 132 can be changed depending on the shape of the internal electrodes 121, 122 and other purposes.
[0038] The interface layers 141, 142 can be disposed between the ends of the dielectric layer 111 and the base electrode layers 131a, 132a. That is, the interface layers 141, 142 can include a first interface layer 141 disposed between the third surface 3 and the first base electrode layer 131a and a second interface layer 142 disposed between the fourth surface 4 and the second base electrode layer 132a. The first interface layer 141 can be disposed so as to contact the third surface 3, and the second interface layer 142 can be disposed so as to contact the fourth surface 4. The interface layers 141, 142 are basically disposed on the ends of the dielectric layer 111, but can also cover a part of the internal electrodes 121, 122. In addition, when observing the cross sections in the first and second directions, the interface layers 141, 142 may completely cover the ends of one or more internal electrodes 121, 122, but since the internal electrodes also extend in the third direction, the base electrode layers 141a, 142a may be in direct contact with the internal electrodes 121, 122 to ensure electrical connection between the internal electrodes 121, 122 and the external electrodes 131, 132.
[0039] The basic electrode layer and the interface layer will be described in more detail below with reference to Fig. 5. The K1 region shown in Fig. 5 shows an enlarged view of a portion of the first basic electrode layer 131a and the first interface layer 141, but the first basic electrode layer 131a and the second basic electrode layer 132a have similar configurations, and the first interface layer 141 and the second interface layer 142 have similar configurations, so the description of the first basic electrode layer 131a and the first interface layer 141 includes the description of the second basic electrode layer 132a and the second interface layer 142.
[0040] According to an embodiment of the present invention, the interface layer 141 may include a first glass containing Ba, Zn, and Si. The Ba, Zn, and Si contained in the first glass may each exist in the form of an oxide. The interface layer 141 may include the first glass as a main component, and may also include a portion of the components contained in the dielectric layer 111, the internal electrode 121, and / or the base electrode layer 131a. For example, the interface layer 141 may further include one or more of Mg, Al, Cu, Ca, B, and Sr.
[0041] The fact that the interface layer 141 contains the first glass as a main component means that the interface layer 141 does not contain any intentionally added metal components, except for metals diffused from the internal electrode 121 and the basic electrode layer 131a. Thus, the interface layer 141 may contain Ba, Zn, and Si as main components. In one embodiment, the total mole number of Ba, Zn, and Si relative to the total mole number of the remaining elements excluding oxygen among the elements constituting the interface layer 141 may be 0.5 or more.
[0042] The basic electrode layer 131a may include a metal 31. The metal 31 included in the basic electrode layer 131a may include Cu, Ni, Ag, Pd, Al, Sn, and / or an alloy including these. The metal 31 included in the basic electrode layer 131a may include Cu or may include Cu as a main component, but the present invention is not limited thereto.
[0043] The basic electrode layer 131a may include a second glass 32. The second glass 32 may have a form dispersed in the metal 31. The second glass 32 may include Ba and Si, and more preferably, the second glass 32 may include Ba, Zn, and Si. The Ba, Zn, and Si contained in the second glass may each exist in an oxide form. In an embodiment, at least a portion of the second glass 32 may be in contact with the first glass. This may improve the bonding strength between the basic electrode layer 131a and the interface layer 141.
[0044] As described above, the Si contained in the first glass and the second glass functions as a network former and has strong corrosion resistance, which can prevent the corrosion of the glass by the plating solution and the resulting penetration of the plating solution. However, Si has a high softening temperature and low wettability with metals such as Cu. Therefore, if the second glass 32 is made only of Si oxide, the second glass 32 cannot fully fill the voids in the basic electrode layer 131a, and such voids may become moisture-resistant penetration paths through which moisture from the outside penetrates into the main body 110.
[0045] Ba and Zn contained in the first glass and the second glass may function as a network modifier. Ba and Zn have inferior corrosion resistance compared to Si, but may play a role in lowering the softening temperature and improving the sealing property between the base electrode layer 131a and the interface layer 141. In an embodiment, the first glass and the second glass may further include one or more of Al, Mg, Ca, and Sr, respectively. Al, Mg, Ca, and Sr may function as a network modifier together with Ba and Zn.
[0046] On the other hand, since the basic electrode layer 131a is disposed in contact with the plating layer, the second glass 32 contained in the basic electrode layer 131a has more important corrosion resistance properties than the first glass contained in the interface layer 141. For this reason, it may be preferable that the second glass 32 has a higher Si concentration (at%) than the first glass. Since the interface layer 141 is disposed inside the basic electrode layer 131a and is not disposed in contact with the plating layer, it may be preferable that the first glass has a higher Ba concentration (at%) than the second glass in order to achieve sealing properties.
[0047] As a result, when the average molar ratio (Ba / Si) of Ba to Si contained in the first glass is M1 and the average molar ratio (Ba / Si) of Ba to Si contained in the second glass is M2, M1>M2 can be satisfied. That is, the interface layer 141 including the first glass having a relatively high average molar ratio of Ba to Si can effectively seal the surface of the body 110, and the base electrode layer 131a including the second glass having a relatively low average molar ratio of Ba to Si can effectively suppress the penetration of a plating solution.
[0048] According to an embodiment of the present invention, the above M1 and M2 may satisfy M1 / M2≧1.5. When M1 / M2 is 1.5 or more, the effect of improving the corrosion resistance and sealing property of the present invention may be more significant. That is, if M1 is too low relative to M2, the sealing property of the interface layer 141 may be reduced, and if M2 is too high relative to M1, the corrosion resistance of the base electrode layer 131a may be reduced.
[0049] The upper limit of M1 / M2 does not need to be particularly limited, but may satisfy, for example, M1 / M2≦83. If M1 is too high, the first glass of the interface layer 141 may re-soften and move away from its original position during the firing process of the basic electrode layer 131a, which may reduce the surface sealing property of the body 110. In addition, if M1 / M2 exceeds 83, a significant difference in firing behavior may occur due to the softening temperature difference between the first glass and the second glass, which may reduce the effect of improving the corrosion resistance and sealing property of the present invention.
[0050] There is no need to limit M1 and M2 in particular, and M1 / M2 is 1.5 or more. However, M1 is preferably 0.2 or more and 3.5 or less. If M1 is less than 0.2, the effect of improving the sealing property of the present invention is small, and if M1 exceeds 3.5, the above-mentioned re-softening phenomenon of the first glass may occur.
[0051] Moreover, the M2 is preferably 0.01 or more and less than 0.2. If the M2 is less than 0.01, the above-mentioned difference in sintering behavior may occur, and if the M2 exceeds 0.2, the effect of improving the corrosion resistance of the present invention is small.
[0052] An example of a method for measuring M1 and M2 will be described. First, images of the cross sections in the first and second directions passing through the center of the third direction of the main body 110 are obtained by photographing them with a scanning electron microscope (SEM). Next, the content (at%) of Si element and the content (at%) of Ba element are measured at any point in the first glass by energy dispersive spectroscopy (EDS), and the measured content of Ba element is divided by the content of Si element to obtain the molar ratio of Ba to Si. After performing such EDS measurement at five or more arbitrary points in the first glass, the M1 can be measured by taking the average value of the measured molar ratio of Ba to Si. Also, after measuring the content (at%) of Si element and the content (at%) of Ba element at any point in the second glass by energy dispersive spectroscopy (EDS), the measured content of Ba element is divided by the content of Si element to obtain the molar ratio of Ba to Si. After performing such EDS measurement at five or more arbitrary points in the second glass, the M2 can be measured by taking the average value of the measured molar ratio of Ba to Si.
[0053] In one embodiment, the average molar ratio of Zn to Si (Zn / Si) contained in the first glass may be greater than the average molar ratio of Zn to Si (Zn / Si) contained in the second glass. Zn, like Ba, can play a role in achieving sealing properties. That is, the interface layer 141 including the first glass having a relatively high average molar ratio of Zn to Si can effectively seal the surface of the body 110, and the base electrode layer 131a including the second glass having a relatively low average molar ratio of Zn to Si can effectively suppress the penetration of a plating solution.
[0054] The thickness of the interface layer 141 is not particularly limited. However, the average thickness ti of the interface layer 141 is preferably more than 2 μm and not more than 8 μm. If the average thickness ti of the interface layer 141 is 2 μm or less, the effect of improving the sealing property of the present invention is small. Also, if the average thickness ti of the interface layer 141 exceeds 8 μm, the electrical connection between the internal electrode 121 and the base electrode layer 131a may be reduced, which may result in a reduction in the capacity of the multilayer electronic component 100. The average thickness ti of the interface layer 141 means the average size of the interface layer 141 in the second direction. The average thickness ti of the interface layer 141 can be measured by obtaining an image of a cross section in the first direction and the second direction passing through the center of the body 110 in the third direction by a scanning electron microscope (SEM), measuring the thickness at multiple points, for example, five points equally spaced in the first direction, of the interface layer 141 disposed on one dielectric layer 111, and then averaging the thicknesses. Furthermore, by performing such average value measurements on interface layers 141 disposed on five or more dielectric layers 111 each and then measuring the average value (i.e., measuring at a total of 25 or more points), the average thickness of interface layer 141 can be more generalized.
[0055] The plating layers 131b and 132b can improve mounting characteristics. The type of the plating layers 131b and 132b is not particularly limited, and may be a plating layer containing Ni, Sn, Pd, Cu and / or an alloy containing these, and may be formed of multiple layers. The plating layers 131b and 132b may be, for example, a Ni plating layer or a Sn plating layer, and may be in a form in which a Ni plating layer and a Sn plating layer are formed in sequence. The plating layers 131b and 132b may also include multiple Ni plating layers and / or multiple Sn plating layers.
[0056] Meanwhile, although not shown, a conductive resin layer containing a metal and a resin may be disposed between the base electrode layers 131a, 132a and the plating layers 131b, 132b, if necessary.
[0057] There is no need to particularly limit the overall size of the multilayer electronic component 100. For example, the size of the multilayer electronic component 100 in the second direction can be 0.1 mm to 4.5 mm, the size of the multilayer electronic component 100 in the third direction can be 0.05 mm to 3.2 mm, and the size of the multilayer electronic component 100 in the first direction can be 0.05 mm to 2.5 mm.
[0058] An example of a method for manufacturing the multilayer electronic component 100 described above will now be described.
[0059] First, a ceramic powder for forming the dielectric layer 111 is prepared. An example of the ceramic powder is BaTiO3 powder. The BaTiO3 powder can be synthesized by reacting a titanium raw material such as titanium dioxide with a barium raw material such as barium carbonate. The ceramic powder can be synthesized by, for example, a solid phase method, a sol-gel method, a hydrothermal synthesis method, or the like, but the present invention is not limited thereto.
[0060] Next, the prepared ceramic powder is dried and pulverized, and then an organic solvent such as ethanol and a binder such as polyvinyl butyral are mixed to prepare a ceramic slurry. The ceramic slurry is then coated on a carrier film and dried to prepare a ceramic green sheet.
[0061] Next, an internal electrode pattern is formed by printing an internal electrode conductive paste containing metal powder, binder, etc., on the ceramic green sheet to a predetermined thickness by screen printing, gravure printing, or the like.
[0062] Thereafter, the ceramic green sheet on which the internal electrode pattern is printed is peeled off from the carrier film, and then a predetermined number of ceramic green sheets on which the internal electrode pattern is printed are stacked and pressed to form a ceramic laminate, and the ceramic laminate is cut to a predetermined chip size. Binders and the like contained in the cut chips may be removed preferably through a binder removal process. The conditions of the binder removal process may vary depending on the type of binder used, and are not particularly limited. Thereafter, the binder-removed chip may be fired at a temperature of 1000° C. to 1400° C. to form the body 110 including the dielectric layer 111 and the internal electrodes 121 and 122.
[0063] Next, an interface layer paste, which is a mixture of a first glass frit, a binder, and a solvent, is applied to the third and fourth surfaces 3 and 4 of the main body 110, and then fired to form the interface layers 141 and 142. The method of applying the interface layer paste to the main body is not particularly limited, and any known method such as dipping, transfer, or vapor deposition can be used.
[0064] The first glass frit may contain BaO, ZnO and SiO2, and may further contain Al2O3, MgO, CaO, SrO, etc. as necessary. At this time, the contents of BaO and SiO2 added to the interface layer paste may be adjusted so that the Ba / Si average molar ratio (M1) of the interface layers 141, 142 after firing is 0.2 to 3.5. For example, based on 100 moles of the entire first glass frit, BaO may be 5 moles to 50 mole parts by weight, ZnO may be 1 mole to 40 mole parts by weight, and SiO2 may be 5 moles to 15 moles, but the present invention is not limited thereto. The interface layer paste may be fired at a temperature of, for example, 550°C to 750°C.
[0065] Before forming the base electrode layers 131a, 132a, it is preferable to polish both sides in the second direction of the main body 110 on which the interface layers 141, 142 are formed in order to bring the internal electrodes 121, 122 and the base electrode layers 131a, 132a into contact with each other. The method of polishing both sides in the second direction of the main body 110 on which the interface layers 141, 142 are formed does not need to be particularly limited, but for example, methods such as barrel polishing, sandblasting, and / or laser polishing can be used.
[0066] Thereafter, a paste for a base electrode layer obtained by mixing metal powder, a second glass frit, a binder, and a solvent is applied onto the interface layers 141 and 142, and then fired to form the base electrode layers 131a and 132a. The second glass frit can contain BaO, ZnO, and SiO2, and can further contain Al2O3, MgO, CaO, SrO, etc. as required. At this time, the contents of BaO and SiO2 added to the paste for the base electrode layer can be adjusted so that the Ba / Si molar ratio of the base electrode layers 131a and 132a after firing is, for example, 0.01 or more and less than 0.2. For example, based on 100 parts by weight of the entire second glass frit, BaO can be 1 mol to 10 mol, ZnO can be 1 mol to 10 mol, and SiO2 can be 30 mol to 70 mol, but the present invention is not limited thereto. On the other hand, since the paste for the base electrode layer has a higher SiO2 content than the paste for the interface layer, it can be preferably fired at a temperature higher than the temperature at which the paste for the interface layer is fired. For example, it can be fired at a temperature of 750°C to 900°C, but the present invention is not limited thereto.
[0067] There is no particular need to limit the method for forming the plating layers 131b and 132b. For example, an electrolytic plating method and / or an electroless plating method can be used.
[0068] However, the above-described manufacturing method is an example, and the manufacturing method of the multilayer electronic component 100 is not limited to the above-described manufacturing method.
[0069] (Experimental Example) <Reliability Evaluation by M1 / M2> The following sample number 1 was manufactured by the following method. First, BaTiO3 powder, an organic solvent such as ethanol, and a binder such as polyvinyl butyral were mixed to prepare a ceramic slurry, and then the ceramic slurry was applied onto a carrier film and dried to prepare a ceramic green sheet. Next, a conductive paste for internal electrodes containing Ni powder, a binder, etc. was printed on the ceramic green sheet to a predetermined thickness to form an internal electrode pattern, and the ceramic green sheet on which the internal electrode pattern was formed was stacked and cut. Then, the stacked chip was subjected to a binder removal and firing process to form a main body.
[0070] Thereafter, an interface layer paste, which was a mixture of the first glass frit, a binder, and a solvent, was applied to the third and fourth surfaces 3, 4 of the main body 110, and then fired at 650 to 750° C. to form interface layers 141, 142. The contents of BaO, ZnO, and SiO2 contained in the interface layer paste were 5 to 50 parts by mole by weight of BaO, 1 to 40 parts by mole by weight of ZnO, and 5 to 15 moles of SiO2, based on 100 moles of the entire first glass frit.
[0071] Next, a basic electrode layer paste, which was a mixture of Cu powder, a second glass frit, a binder, and a solvent, was applied onto the interface layer, and then fired at 700 to 850° C. to form a basic electrode layer. The contents of BaO, ZnO, and SiO2 contained in the basic electrode layer paste were 1 mol to 10 mol of BaO, 1 mol to 10 mol of ZnO, and 30 mol to 70 mol of SiO2, based on 100 parts by weight of the second glass frit in total.
[0072] After that, a Ni plating layer and a Sn plating layer were sequentially formed on the basic electrode layer to prepare a sample chip of sample number 1. The sample chip of sample number 1 was manufactured in 2012 size (size in the second direction is about 2.0 mm, size in the third direction is about 1.2 mm) with a capacitance of 10 uF.
[0073] Samples 2 to 8 were produced in the same manner as sample 1 described above, but the contents of BaO, ZnO, and SiO2 added to the interface layer paste were changed so that the Ba / Si average molar ratio (M1) of the interface layer after firing was different from that of sample 1. Specifically, the content of BaO relative to the SiO2 added to the interface layer paste increased from sample 2 to sample 8.
[0074] Then, the cross sections of the sample chips of each sample number in the first and second directions passing through the center of the third direction were photographed with a scanning electron microscope (SEM) to obtain images, and then energy dispersive spectroscopy (EDS) was performed on the first glass included in the interface layer to measure the molar ratio of Ba to Si. After such EDS measurement was performed at any five points in the first glass, the M1 was measured by taking the average value of the measured molar ratios of Ba to Si. In the same manner, EDS measurement was performed at any five points in the second glass included in the base electrode layer, and the M2 was measured by taking the average value of the measured molar ratios of Ba to Si. Then, the M1 / M2 values of the sample chips of each sample number are listed in Table 1 below.
[0075] After this, for 20 sample chips per sample number, a voltage of 1.5 Vr was applied for 24 hours under conditions of a temperature of 85°C and a relative humidity of 85%, and if even one sample showed an IR (insulation resistance) value that had fallen to 10% or less of the initial IR value, it was indicated as "X", and if none of the samples showed this, it was indicated as "O".
[0076] [Table 1]
[0077] Referring to Table 1 above, it can be seen that samples 3 to 7 with M1 / M2 of 1.5 or more did not fail when evaluating moisture resistance reliability. This is because the interface layer seals the surface of the body, preventing moisture from penetrating into the inside of the body. However, it can be seen that samples 1 and 2 with M1 / M2 less than 1.5 and sample 8 with M1 / M2 exceeding 83 failed when evaluating moisture resistance reliability.
[0078] <Reliability evaluation based on interface layer thickness> In order to evaluate the reliability depending on the thickness of the interface layer, sample chips of sample numbers 9 to 13 were produced. First, sample number 9 was produced in the same manner as sample number 1, but the basic electrode layer was formed immediately without applying the interface layer paste.
[0079] Samples 10 to 13 were manufactured in the same manner as sample 6, and had an M1 / M2 of 15.9. However, the amount of paste for the interface layer applied was adjusted for each sample so that the average thickness of the interface layer after firing was different from each other. The average thickness of the interface layer was measured by taking an image of a cross section in the first direction and the second direction passing through the center of the third direction of the main body using a scanning electron microscope (SEM), and then measuring the thickness at five equally spaced points in the first direction of the interface layer disposed on one dielectric layer 111, and calculating the average value. The average value measurement was also performed on the interface layers disposed on five dielectric layers 111, and the average thicknesses of the interface layer 141 measured at a total of 25 points are shown in Table 2 below.
[0080] After this, the capacity and reliability of the sample chips of each sample number were evaluated. First, the capacity of a total of 30 sample chips for each sample number was measured using an LCR meter. If even one of the 30 sample chips had a measured capacity of less than 95% of the nominal capacity, it was marked with an "X" and if none of them had any, it was marked with an "O". The reliability evaluation was the same as the above method, with even one defective sample with an IR (insulation resistance) value of 10% or less of the initial IR value marked with an "X" and none of them marked with an "O".
[0081] [Table 2]
[0082] Referring to Table 2 above, it can be seen that when the average thickness of the interface layer is 2 μm or less, a failure occurs during the evaluation of moisture resistance reliability. This is because the interface layer does not adequately seal the surface of the body. In addition, it can be seen that when the average thickness of the interface layer exceeds 8 μm, the capacity decreases. Therefore, it is preferable that the average thickness of the interface layer is more than 2 μm and not more than 8 μm.
[0083] The present invention is not limited by the above-described embodiments and the attached drawings, but is limited by the appended claims. Therefore, various substitutions, modifications and changes can be made by a person having ordinary skill in the art within the scope of the technical idea of the present invention described in the claims, and these also belong to the scope of the present invention.
[0084] In addition, the expression "one embodiment" does not mean the same embodiment, but is provided to emphasize and describe each unique feature that is different from the others. However, the above-mentioned one embodiment does not exclude being realized in combination with the features of another embodiment. For example, even if a matter described in a specific embodiment is not described in another embodiment, it can be understood as being related to the other embodiment unless there is a description in the other embodiment that is opposite or contradictory to the matter.
[0085] Furthermore, the terms "first", "second", etc. are used to distinguish one component from another and do not limit the order and / or importance of the components. In some cases, a first component may be named as a second component, and similarly, a second component may be named as a first component, without departing from the scope of the invention. [Explanation of symbols]
[0086] 100 Multilayer electronic components 110 Main unit 111 Dielectric layer 112, 113 Cover part 114, 115 Margin 121, 122 Internal electrode 131, 132 External electrode 131a, 132a Basic electrode layer 131b, 132b plating layer 141, 142 interfacial layer 31 metal 32 Second Glass
Claims
1. a body including dielectric layers and internal electrodes interleaved with the dielectric layers; an outer electrode including a base electrode layer connected to the inner electrode; an interface layer disposed between an end of the dielectric layer and the base electrode layer; the interface layer comprises a first glass comprising Ba, Zn and Si; the base electrode layer comprises a second glass comprising Ba and Si; When the average molar ratio of Ba to Si (Ba / Si) contained in the first glass is M1 and the average molar ratio of Ba to Si (Ba / Si) contained in the second glass is M2, The multilayer electronic component, wherein M1 and M2 satisfy M1 / M2≧1.
5.
2. 2. The multilayer electronic component according to claim 1, wherein M1 is equal to or greater than 0.2 and equal to or less than 3.
5.
3. 2. The multilayer electronic component according to claim 1, wherein M2 is equal to or greater than 0.01 and less than 0.
2.
4. 2. The multilayer electronic component according to claim 1, wherein M1 and M2 satisfy M1 / M2≦83.
5. 2. The multilayer electronic component according to claim 1, wherein the average thickness of the interface layer is more than 2 μm and not more than 8 μm.
6. the second glass contains Zn; 2. The multilayer electronic component according to claim 1, wherein an average molar ratio of Zn to Si (Zn / Si) contained in the first glass is greater than an average molar ratio of Zn to Si (Zn / Si) contained in the second glass.
7. The laminated electronic component according to claim 1 , wherein at least a portion of the second glass is in contact with the first glass.
8. The multilayer electronic component according to claim 1 , wherein each of the first glass and the second glass further contains one or more of Al, Mg, Ca, and Sr.
9. 2. The multilayer electronic component according to claim 1, wherein the total mole number of Ba, Zn and Si relative to the total mole number of remaining elements excluding oxygen, among the elements constituting said interface layer, is 0.5 or more.
10. The multilayer electronic component according to claim 1 , wherein the base electrode layer includes a metal including Cu.
11. The multilayer electronic component according to claim 1 , wherein the external electrodes include a plating layer disposed on the base electrode layer.
12. The multilayer electronic component according to claim 1 , wherein the base electrode layer is in direct contact with the internal electrode.
Citation Information
Cited By
Game machine
JP2025092651A
Game machine
JP2025092652A
Game machine
JP2025092653A
Game machine
JP2025092654A
Game machine
JP2025102874A